1992
DOI: 10.1288/00005537-199206000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Noise‐induced hearing loss in children

Abstract: Occupational noise exposure remains the most commonly identified cause of noise-induced hearing loss (NIHL), but potentially hazardous noise can be encountered during leisure-time activities. NIHL in the pediatric population has received scant attention. This study focuses on 114 children and adolescents (ages 19 and under: 90.3% males) who were diagnosed as having probable NIHL on the basis of history and audiometric configuration. In 42 children the loss was unilateral, while the remaining 72 had sensorineur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
4

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 19 publications
1
50
0
4
Order By: Relevance
“…Trauma to the nervous system, damaging noise levels, and ototoxic drugs can all place a child at risk of developing acquired hearing loss. 6,7 Otitis media is a common cause of usually reversible hearing loss. Certain physical findings, historical events, and developmental conditions may indicate a potential hearing problem.…”
Section: Risk Indicators For Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma to the nervous system, damaging noise levels, and ototoxic drugs can all place a child at risk of developing acquired hearing loss. 6,7 Otitis media is a common cause of usually reversible hearing loss. Certain physical findings, historical events, and developmental conditions may indicate a potential hearing problem.…”
Section: Risk Indicators For Hearing Lossmentioning
confidence: 99%
“…Children with hearing loss should also be monitored for developmental and behavioral problems (attentiondeficit/hyperactivity disorder, autism, learning disabilities) and referred for Should correctly localize to sound presented in a horizontal plane, begin to imitate sounds in own speech repertoire or at least reciprocally vocalize with an adult [7][8][9][10][11][12] Should correctly localize to sound presented in any plane, should respond to name, even when spoken quietly [13][14][15] Should point toward an unexpected sound or to familiar objects or persons when asked [16][17][18] Should follow simple directions without gesture or other visual cues; can be trained to reach toward an interesting toy at midline when a sound is presented [19][20][21][22][23][24] Should point to body parts when asked; by 21 mo, can be trained to perform play audiometry additional evaluation when necessary. Health care professionals can use screening tools to evaluate young children periodically for such concerns (Table 7) and refer for additional evaluation when concerns arise.…”
Section: Follow-up and Diagnostic Testingmentioning
confidence: 99%
“…Occupational noise exposure remains the most commonly identified cause of NIHL but potentially hazardous noise can be encountered during recreational activities [1].…”
Section: Introductionmentioning
confidence: 99%
“…Noise exposure can affect health and cochlear function [3][4][5][6]. Long et al [4] noticed changes in oxygenation and intracerebral pressure accompanying noise bursts and Gadeke et al [7] observed infant sleep disturbances: these observations are important, because sudden changes in intracerebral perfusion may lead to cerebral haemorrhage [8] and disturbances in sleep cycles due to noise may provoke abnormal hormone production [9].…”
Section: Introductionmentioning
confidence: 99%